The Influence Of Cultural Factors On The Use Of Nonverbal Communication (Open Academia: Journal of Scholarly Research, 2025)
Nonverbal communication plays a key role in intercultural interactions. Culture influences how people use gestures, facial expressions, postures, intonation, and other nonverbal elements to convey information. This article is dedicated to analyzing the impact of cultural factors on the use of nonverbal communication and exploring differences in the perception and interpretation of nonverbal cues across cultures. Special attention is given to the significance of nonverbal communication in intercultural communication and its role in successful interaction